Overview of Drug Planning and Procurement Using ABC and Ven Analysis at Salawu Community Health Center - Rahma, Ayu; Putra, Arestuna Sapari; Ahmad, Fina (LPPM STIKes Muhammadiyah Ciamis, 2025)
Medicine is a basic component of health services, the disease suffered by patients can be measured by the level of recovery by administering medicine, the Community Health Center as a functional organization has the role of providing health maintenance, prevention, healing and health restoration services. One of the main programs at the community health center is a treatment program, so it is necessary to have sufficient medication available at the community health center. This research was conducted at the Salawu Community Health Center. The aim of this research was to determine the grouping of drugs based on ABC investment analysis, ABC usage analysis and VEN analysis. The research method used was quantitative descriptive using secondary data in the form of LPLPO and supported by primary data from the interview process. The results of this research included drugs in group A based on investment totaling 23 items, group B totaling 31 items and group C 50 items, whereas in the results of the ABC analysis the level of use for group A was 14 items, group B 21 items and group C 69 items. Then the results of the VEN analysis in group V were 13, group E had 64 items and group C had 50 items.